AB018. The effect of immediate surgical bipolar PlasmaKinetic transurethral resection of the prostate on prostatic hyperplasia with acute urinary retention - He, Leye (Transl Androl Urol, 2016)
BACKGROUND: In the present study, we evaluated the safety and efficacy of immediate surgical bipolar PlasmaKinetic transurethral resection of the prostate (PK-TURP) for patients with benign prostatic hyperplasia (BPH) with acute urinary retention (AUR). METHODS: We conducted a retrospective analysis of clinical data of BPH patients who received PK-TURP. A total of 1,126 BPH patients were divided #I# AUR (n=348) and non-AUR groups (n=778). RESULTS: After the urethral catheters were removed, the urine white blood cell (WBC) count in the AUR group significantly increased compared with the non-AUR group (P<0.01). However, there was no significant difference in international prostate symptom score, painful urination, and maximal urinary flow rate. The duration of hospitalization of the AUR group was longer than that of the non-AUR group (P<0.001). A total of 87.1% (303/348) patients in the AUR group and 84.1% (654/778) patients in the non-AUR group completed all of the postoperative follow-up visits. The incidence of urinary tract infection in the AUR group within 3 months after surgery was significantly higher than that in the non-AUR group (P<0.01). The incidence of temporary urinary incontinence in the AUR group did not exhibit significant difference. During 3–12 months after surgery, there were no significant differences in major complications between the two groups. Multivariate regression analyses showed that age, postvoid residual, maximal urinary flow rate, diabetes, and hypertension, but not the presence of AUR, were independent predictors of IPSS post-K-URP. CONCLUSIONS: In conclusion, immediate PK-URP surgery on patients accompanied by AUR was safe and effective.